Development of copper-based catalyst for the electroproduction of multi-carbon molecules from CO2 - Lai, Yin Hui (Nanyang Technological University, 2023)
Electrochemical CO2 conversion into value-added chemicals and fuel have demonstrated to be a potential method to reach carbon neutrality. Among various metal catalysts, copper-based catalysts are discovered to have the ability to produce multi-carbon (C2+) molecules from CO2 reduction reaction (CO2RR), such as ethylene, ethanol, and propanol. Recently, copper-based metal-organic frameworks (Cu-MOFs) have garnered huge interest due to their well-defined structure and large surface area, which provides large number of active sites for CO2RR. However, thus far, nanosized Cu-MOFs and MOFs on conductive supports for catalytic applications were rarely reported. Herein, we developed Cu-MOF with different particle sizes ranging from 59.3 nm to 1.11 µm (denoted as Small Cu-MOF, Hybrid Cu-MOF, and Big Cu-MOF), and the addition of food waste-derived carbon to Cu-MOF with various composition ratios (denoted as Cu-MOF/low-carbon, Cu-MOF/medium-carbon, and Cu-MOF/high-carbon, respectively). The Small Cu-MOF exhibited a relatively high performance for electrocatalytic reduction of CO2 to C2+ with a FE of 55.7% at a current density of 300 mA cm−2 and at the potential of −1.08 V vs RHE in 1 M KHCO3 solution. The developed Cu-MOF/high-carbon exhibited 33.0% higher partial current density to C2+ at a potential of −0.93 V vs RHE than Small Cu-MOF. Scanning electron microscopy characterization suggested that the enhanced electrochemical performance may be caused by the addition of carbon that aids in the dispersion of Cu-MOF nanospheres onto the carbon support. This in turn favors the creation of highly active sites for CO2 adsorption and activation.